The role of total hip arthroplasty in the treatment of patients with floating hip after polytrauma - S.O. Guryev; P.V. Tanasiienko; I.V. Kovalyshyn (Bolʹ, Sustavy, Pozvonočnik)
Background. According to experts, the mortality rate in polytrauma with severe injuries of the pelvis and thigh reaches 80 %. Our study purposed to test and evaluate the effectiveness of total hip arthroplasty (THA) in patients with a floating hip as a result of polytrauma. Materials and methods. We analyzed the treatment of 77 cases of ipsilateral hip fractures as a result of polytrauma. Patients were divided into two groups according to the floating hip treatment method. The first group consisted of 43 subjects with a floating hip as a result of polytrauma, treated with internal metal osteosynthesis, and the second — 34 victims, whose treatment was carried out with THA. The results of treatment were assessed using the Harris scale 6 months after surgery. Results. In the first group, a satisfactory treatment result was most often confirmed, corresponding to a score of 70–79 points on the Harris scale (41.9 % of patients). A good treatment result was found in 30.2 % of cases in the first group, and in the second group, such a result was established most often (in 61.8 % of subjects). An unsatisfactory treatment result was found in only 2.9 % of cases in the second group. A reverse trend was observed among patients with an excellent treatment outcome. If 9.3 % of patients in the first group achieved an excellent result, then in the second group, the number was twice as high. Conclusion. Despite the existing treatment strategies for patients with polytrauma, in patients with a floating hip we obtained significantly better treatment results when using THA. Such functional results are associated with the peculiarities of providing medical care in the shock period and the period of unstable adaptation to the course of polytrauma, as well as the use of damage control tactics, which significantly prolongs the treatment time of such victims. Thus, the use of THA as an important treatment method for patients in this category deserves further, more controlled comparative research.